In viaggio per il Congresso di Vienna Lettere di Daniello Berlinghieri a Anna Martini, con un percorso tra le fonti archivistiche in appendice - Tourres, Josiane; Innocenti, Barbara; Lombardi, Marco (Biblioteca di Studi di Filologia Moderna, 2020)
The volume focuses on the transcription of the unpublished letters of Daniello Berlinghieri to Anna Martini during Berlinghieri's mission to the Congress of Vienna for the Order of Malta. The critical apparatus aims to reconstruct the stages of the journey on a documentary basis, and contextualize characters and events evoked from a biographical, literary and historical-cultural standpoint, including them into the Microhistory and Macrohistory of which they were the protagonists. The epistolary is translated here in French.